Changes in the Distribution of Intrauterine Microbiota May Attribute to Immune Imbalance in the CBA/J×DBA/2 Abortion-Prone Mice Model - Bai, Shiyu; Huang, Bingqian; Fu, Shuai; Zhu, Menglan; Hu, Lihao; Zhu, Liqiong; Chen, Manqi; Zhang, Zicheng; Tan, Jianping; Zhang, Jianping; Chen, Hui (Frontiers in Immunology, 2021)
Background: Female Genital Tract (FGT) is an important micro-ecological area. Microbiota in the lower reproductive tract may subsequently invade the uterine cavity during embryo implantation and produce immune responses. CBA/J×DBA/2 mating combination has been widely used as an abortion-prone model but whether microbiota existed in their uterine cavity remains unclear. Objective: To investigate the relationship between the distribution of microbiota in the uterine cavity of CBA/J×DBA/2 abortion-prone mouse model and the immune imbalance of the maternal-fetal interface. Methods: Female CBA/J mice were paired with male DBA/2 mice to develop an abortion-prone model (BA group), and with male BALB/c mice as a standard pregnancy model (BC group). The non-pregnant ones were served as the control group (C group). Uterine flushing fluid and sera were collected on day 13.5 of pregnancy. 16S rRNA sequencing technology was used to analyze the distribution of intrauterine microbiota. Phylogenetic Investigation of Communities were conducted to predict the microbiota functions by Reconstruction of Unobserved States (PICRUST) and Kyoto Encyclopedia of Genes and Genomes (KEGG). The serum IL 10, INF-γ, and TNF-α levels were examined using Enzyme-linked immunosorbent assay (ELISA) method. Results: The α diversity (p = 0.00077) had significant differences among three groups. Proteobacteria was the most dominant phylum in C group (mean = 83.21%) and BA group (mean = 43.23%). Firmicutes was dominant in BC group (mean=46.4%), as well as the second dominant one in C group (mean=12.63%) and BA group (mean=40.55%). Microbiota functions were associated with metabolism and immune response through the NOD-like receptor signaling pathway. The serum IL 10 level in BA group were significantly lower than that in BC group (10.14±1.90 pg/ml, n=8; vs 19.03±1.82 pg/ml, n=10; p=0.004). The serum TNF-α and INF-γ level in BA group were significantly higher than BC group (523.1±58.14 pg/ml, n=8 vs 310.3±28.51 pg/ml, n=10, p=0.0029; 69.22±5.38 pg/ml, n=8 vs 50.85±2.45 pg/ml, n=10, p=0.0042.) Conclusion: Microbial communities were colonized in uterine cavity of CBA/J mice both at non-pregnant stage and pregnant stage when mated with both BALB/c and DBA/2 male mice. The differentially abundant microbiome may be attributed to the immune tolerance through binding to the NOD-like receptor.